Do Online Illicit Drug Market Exchanges Afford Rationality?. (December 2020) - Childs, Andrew; Coomber, Ross; Bull, Melissa
Rational choice perspectives have been the dominant models used for conceptualizing the nature of exchanges in illicit drug markets, but various critiques have found these abstracted assumptions inadequate for understanding concrete illicit drug market activity. Considerably less, however, is known about key aspects of rationality in exchanges within online drug markets. Recognizing the inadequacies of an underlying homo economicus, we instead conceive drug market exchanges as complex assemblages, noting how exchanges are reconstructed in online spaces, and technological affordances may facilitate elements of rationality in drug exchanges. Adopting these notions allows us to argue that aspects of rationality can potentially contribute to an understanding of exchange practices in online markets, and that online channels can afford assumptions of utility-maximization, rich market information to guide decision-making, and anonymity in the exchange. In addition, consideration is given to the structural variability of online illicit drug markets, and that the affordance of rationality should be considered across a spectrum of applicability that takes into account the specifics of each dimension of online drug market (i.e. drug cryptomarkets, illicit online pharmacies, and "app-based" drug markets).